Linear magnetoelastic coupling and magnetic phase diagrams of the buckled-kagomé antiferromagnet Cu3Bi(SeO3)2O2Cl - Spachmann, Sven; Berdonosov, P.; Markina, M.; Vasiliev, A.; Klingeler, Rüdiger (Scientific reports, 2022)
Single crystals of Cu$$_3$$Bi(SeO$$_3$$)$$_2$$O$$_2$$Cl were investigated using high-resolution capacitance dilatometry in magnetic fields up to 15 T. Pronounced magnetoelastic coupling is found upon evolution of long-range antiferromagnetic order at $$T_{N}$$ $$= 26.4(3)$$ K. Grüneisen analysis reveals moderate effects of uniaxial pressure on $$T_{N}$$, of 1.8(4) K/GPa, $$-0.62(15)$$ K/GPa and 0.33(10) K/GPa for \parallel a$$, b, and c, respectively. Below 22 K Grüneisen scaling fails which implies the presence of competing interactions. The structural phase transition at $$T_{S}$$ $$= 120.7(5)$$ K is much more sensitive to uniaxial pressure than $$T_{N}$$, with strong effects of up to 27(3) K/GPa ( \parallel c$$). Magnetostriction and magnetization measurements reveal a linear magnetoelastic coupling for $$B\parallel c$$below $$T_{N}$$, as well as a mixed phase behavior above the tricritical point around 0.4 T. An analysis of the critical behavior in zero-field points to three-dimensional (3D) Ising-like magnetic ordering. In addition, the magnetic phase diagrams for fields along the main crystalline axes are reported.
Im Titel sind "3" und "2" jeweils tiefgestellt
Gesehen am 17.06.2022